2010
DOI: 10.1037/a0019124
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness, spiritual instability, mental health symptoms, and well-being: Mediator effects of differentiation of self.

Abstract: The present study tested the theoretical formulation based on Bowenian theory and Volfian theology that differentiation of self (DoS) serves as a mediator variable by which dispositional forgiveness is associated with indices of spiritual and mental health. Data were collected in a sample (N = 213) of graduate students (mean age = 34.46 years) at a Protestant-affiliated university. Results supported the hypotheses with DoS mediating the relationship between dispositional forgiveness and (a) spiritual instabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 56 publications
4
58
0
Order By: Relevance
“…Past research has indicated that higher differentiation is related to a greater capacity to forgive and to lower levels of dating violence (Holeman et al, 2011;Rosen et al, 2001;Sandage & Jankowski, 2010). Our models reflected the nature of these relationships by indicating higher capacities to forgive related to lower levels of offspring dating violence perpetration and victimization.…”
Section: Discussionsupporting
confidence: 66%
“…Past research has indicated that higher differentiation is related to a greater capacity to forgive and to lower levels of dating violence (Holeman et al, 2011;Rosen et al, 2001;Sandage & Jankowski, 2010). Our models reflected the nature of these relationships by indicating higher capacities to forgive related to lower levels of offspring dating violence perpetration and victimization.…”
Section: Discussionsupporting
confidence: 66%
“…In forgiving, people need to tell the truth about the offender and the injustice while transforming unforgiving and retributive responses so they are constructive, prosocial, and can genuinely promote flourishing (Witvliet, 2012). Concerns for victim safety (Gordon, Burton, & Porter, 2004;McNulty, 2010), self-differentiation (Sandage & Jankowski, 2010), self-concept clarity, and self-respect (Luchies, Finkel, McNulty, & Kumashiro, 2010) are important for setting the boundary conditions of a just forgiveness that is morally grounded, promotes responsible healing, and does not excuse, minimize, or tolerate injustice . Empathy and compassion are responses that are typically directed toward others who are victims deserving of help when one has the resources to assist, according to the appraisal model of Goetz, Keltner, and Simon-Thomas (2010).…”
Section: Empathy and Forgivenessmentioning
confidence: 99%
“…Additionally, research has shown that in healthy families, individual family members tend to develop differentiation and skills for affect regulation that are associated with psychological adjustment, well‐being, and self‐control (Sandage & Jankowski, ; Skowron, Wester, & Azen, ). Furthermore, high levels of DoS predict better interpersonal functioning and higher marital satisfaction and quality (Gubbins, Perosa, & Bartle‐Haring, ; Lampis, Busonera, Cataudella, Tommasi, & Skowron, 2016; Peleg, ; Timm & Keiley, ).…”
Section: Introductionmentioning
confidence: 99%